Enhancing pedagogical strategies through technology integration in basic teacher education program - Mpuangnan, Kofi (UIN Raden Mas Said Surakarta, 2023)
This study investigated enhancing pedagogical strategies through technology integration in basic teacher education programs. It sheds light on its significant influence on both educational management and instructional approaches. The investigation centred on experiences within Ghana's College of Education (CoE), contributing insights that align with the objectives of Sustainable Development Goal 4. A mixed-method approach was employed, integrating both quantitative and qualitative methods. The participants of the study consisted of 485 participants (469 tutors and 16 principals) selected from sixteen colleges by using cluster and simple random sampling techniques. Quantitative data were gathered by employing a structured questionnaire, while qualitative data were acquired through semi-structured interviews. The quantitative data underwent analysis using both descriptive and inferential statistics, while the qualitative data were subjected to an inductive analysis approach. The results revealed the noteworthy influence of age, gender, higher qualifications, and professional experience of principals and instructors on technology integration in education. Furthermore, key indicators such as smartphone usage and Microsoft Office 365 tools were found to be insufficient for facilitating technology integration. This inadequacy was attributed to managerial challenges like infrastructural limitations and resistance to change. It was recommended that the Ministry of Education should institute regular in-service training initiatives on technology integration. This step will empower the staff at CoE with the requisite knowledge and competencies to proficiently infuse technology in their roles.